Evaluation of Shape, Roundness, Sphericity and Equality in commercial yellow hard corn (Zea mays L.) and pea (Pisum sativum) grains - Manayay Sánchez, Damián (2016)
It has been evaluated the shape, roundness, sphericity and equanticity of commercial yellow hard corn and dry pea grains, making micronometric measurements in 140 and 100 grains randomly in each quarter, in samples of one kilogram divided into four equal parts respectively.The results indicate that the hard yellow corn is very close to the discoid, it is located between rounded and rounded sub, is of medium sphericity and shows a non spherical equanticity, whereas dry pea has a shape very close to the spherical or equidimensional, Is very rounded, has high sphericity and shows a spherical equanticity.